Methenamine Prophylaxis for Recurrent Urinary Tract Infections in a Tertiary Referral Center. Issue 6 (23rd November 2021) - Wade, Cameron; Lacy, Mary E.; Harris, Lauren; Goldwag, Jordan; Erickson, Deborah R.
Abstract: Introduction: Methenamine hippurate (MH) is a urinary antiseptic, indicated for prophylaxis of recurrent urinary tract infections (UTIs) but with only few and limited studies regarding its efficacy. To help address this knowledge gap we reviewed our experience with MH for UTI prophylaxis, focusing on women with recurrent uncomplicated UTIs. Methods: The University of Kentucky electronic health record was queried to identify adults who were prescribed MH from the urology clinic between January 2013 and January 2019. Charts were reviewed to assess patient-reported UTI frequency, demographics and relevant health factors. Treatment success was defined as 0–1 UTI in 6 months or 0–2 UTIs in 1 year. Results: Of 670 patients prescribed MH, 508 did not meet inclusion criteria. The most common reasons for exclusion were complicated UTI, no return visit, treatment nonadherence and insufficient followup time. The primary study population was 162 women with recurrent uncomplicated UTIs: 41 premenopausal and 121 postmenopausal. Success rates with MH were 83% and 77%, respectively. Success rates were not significantly associated with age, diabetes, immune suppression, high-tone pelvic floor dysfunction or (if postmenopausal) vaginal estrogen use. Exploratory study of patients using intermittent catheterization showed success in 20 of 30 patients (67%). Conclusions: MH had high success rates for premenopausal and postmenopausal women with recurrent uncomplicated UTIs. Patients using catheters had lower success rates. Prospective trials would strengthen the evidence to guide decisions for treatment and insurance coverage.